Perancangan Mesin Penggiling Kopi Dan Penakar Bubuk Kopi Untuk Usaha Mikro Kecil Menengah - Aidil Zamri; Regal Junia Mandora; Yuliarman . (Fakultas Teknik UMSU, 2023)
In micro, small and medium enterprises in coffee grinding and coffee powder dosing. We still see a lot of things manually using measuring spoons and scales, in large quantities it takes a long time to measure. So that the coffee grinder and coffee powder measurer are designed in one machine with a smaller and simpler size, where there are two processes, namely the coffee grinder and the coffee powder measurer. The shaft of the blade of the coffee grinder is designed to have a diameter of 15 mm using bearing number 6002. By using four cutting blades with coffee cutting knife dimensions, 25 mm long and 6 mm wide. In the grinding machine, the coffee is ground into powder with a machine capacity of 73.8 kg/hour. After becoming powder, there is a process in the measuring machine, the coffee powder is measured with the same mass in each package with a machine capacity of 73.8 kg/hour. The driving motor used for the coffee grinder and measuring machine is 2 HP. The rotation speed is 1,400 rpm, with the motor type ML90S-2.